2013
DOI: 10.1111/hel.12062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Ten‐Day Regimen with Esomeprazole, Metronidazole, Amoxicillin, and Clarithromycin for the Eradication of Helicobacter pylori in a High Clarithromycin Resistance Area

Abstract: The 10-days "concomitant" regimen is effective and safe first-line H. pylori treatment, in a high clarithromycin resistance area, although dual antibiotic resistance may compromise its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
4
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 42 publications
5
47
4
1
Order By: Relevance
“…In contrast, in the present study, which was performed in Istanbul, no tetracycline resistance was detected. We detected no amoxicillin or tetracycline resistance in our study, and our results are in accord with those of Georgopoulos et al (17) and Boyanova et al (18) for amoxicillin resistance.…”
Section: Ethical Considerationssupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, in the present study, which was performed in Istanbul, no tetracycline resistance was detected. We detected no amoxicillin or tetracycline resistance in our study, and our results are in accord with those of Georgopoulos et al (17) and Boyanova et al (18) for amoxicillin resistance.…”
Section: Ethical Considerationssupporting
confidence: 93%
“…Our result is higher than the results of Georgopoulos et al (17) (16%) and Boyanova et al (18) (10%) for levofl oxacin resistance rates. This difference could be due to the crowded population, to the geographic location of Istanbul or to the frequent use of this antibiotic for respiratory and/or urinary infections in this area.…”
Section: Financial Supportcontrasting
confidence: 84%
See 2 more Smart Citations
“…Two novel eradication regimens, namely concomitant and hybrid therapy, have proven more effective than triple and sequential therapy in the last few years, particularly in patients with dual-(clarithromycin-and metronidazole-) resistant H. pylori strains [107][108][109][110][111] . Metaanalyses have shown that the outcome of concomitant therapy is duration-dependent [112] .…”
Section: Hybrid and Concomitant Therapymentioning
confidence: 99%